Decision Support System For Employee Assessment At PT. Kupu-Kupu Taman Lestari Using AHP And BARS Methods: Decision Support System For Employee Assessment At PT. Kupu-Kupu Taman Lestari Using AHP And BARS Methods - I Made Dwi Putra Asana; I Gede Iwan Sudipa; I Made Angga Wijaya (Institute of Computer Science (IOCS), 2020)
Employee performance evaluation has an important role in the world of work, especially in the field of tourism as it relates to the decision to be taken by the company. PT. Kupu-Kupu Taman Lestari is a company engaged in the field of tourism and in desperate need of competent employees to achieve corporate goals. Therefore, PT. Kupu-Kupu Taman Lestari sustainable human resources management need to improve the quality of its employees, although previously been applied but for their eventual management turnover is not there anymore management which resulted in no clear and measurable standards, as well as the employees are not motivated to work. One way to manage human resources can be assessed employee assessment based on the criteria that have been determined each weight of importance to the method Analytic Process and behaviorally Anchor Hierarhcy Rating Scale which is used to overcome the problem of subjective assessment employee performance to be more objective. By using these two methods are expected to solve the problem of assessment of employees at PT. Kupu-Kupu Taman Lestari, so that a more objective assessment, recorded, measured and employee motivation.